Primer registro de Abrothrix olivacea (Waterhouse, 1837) en Perú basado en material histórico de Tacna - Cairampoma, Raisa (2024)
Abrotrichini is the sigmodontine tribe with the fewest species in Peru, known only from two species: Abrothrix andina and Ab. jelskii, both distributed in the high Andean regions of Peru above 3000 m in altitude. A detailed review of the morphology of historical specimens collected in the Tacna department and identified as Akodon mollis was conducted. As a result, we found that the examined specimens corresponded to Abrothrix olivacea, a species previously known only from Chile and Argentina. This discovery represents the first record of this species in Peru, extending its distribution range 165 km north of its previous northernmost record in Quebrada Camarones, Arica-Parinacota, Chile. Furthermore, this finding significantly reduces the distribution range of Akodon mollis to the northwestern region of Peru. We also provide key craniodental characters to differentiate species of Abrothrix and Akodon in southwestern Peru and northern Chile. For Peru, this record increases the diversity of mammals to 588 species and rodents to 201 species. In the case of the Tacna department, mammalian diversity increases to 47 species. This work highlights the value of natural history museum collections in enhancing our understanding of species diversity.